Sustainable management of mining operations - Botin, J. A. (Published by Society for Mining, Metallurgy, and Exploration, 2009)
The pressure is on to enhance corporate reputations, achieve higher operational efficiency, improve planning and control, gain access to mineral resources, build trust with stakeholders, attract financing, recruit and retain a quality workforce, and lower costs. Sustainable Management of Mining Operations provides a holistic, practical approach to achieving these goals. The key, say the authors, is to create a culture within the organization that recognizes the value of sustainability by effectively integrating economic, environmental, and social considerations. Each section of this book focuses on sustainable management from a different perspective, management level, or stage of the mine life cycle.
Keywords: Mineral industries -- Management.; Mineral industries -- Environmental aspects.; Sustainable development.; elektronické knihy; electronic books